Absent otoacoustic emissions predict otitis media in young Aboriginal children: A birth cohort study in Aboriginal and non-Aboriginal children in an arid zone of Western Australia - Lehmann, Deborah; Weeks, S.; Jacoby, P.; Elsbury, D.; Finucane, J.; Stokes, A.; Monck, R.; Coates, H. (BioMed Central, 2008)
AbstractBackground: Otitis media (OM) is the most common paediatric illness for which antibiotics areprescribed. In Australian Aboriginal children OM is frequently asymptomatic and starts at a youngerage, is more common and more likely to result in hearing loss than in non-Aboriginal children.Absent transient evoked otoacoustic emissions (TEOAEs) may predict subsequent risk of OM.Methods: 100 Aboriginal and 180 non-Aboriginal children in a semi-arid zone of WesternAustralia were followed regularly from birth to age 2 years. Tympanometry was conducted atroutine field follow-up from age 3 months. Routine clinical examination by an ENT specialist wasto be done 3 times and hearing assessment by an audiologist twice. TEOAEs were measured at ages<1 and 1–2 months. Cox proportional hazards model was used to investigate the associationbetween absent TEOAEs and subsequent risk of OM.Results: At routine ENT specialist clinics, OM was detected in 55% of 184 examinations inAboriginal children and 26% of 392 examinations in non-Aboriginal children; peak prevalence was72% at age 5–9 months in Aboriginal children and 40% at 10–14 months in non-Aboriginal children.Moderate-severe hearing loss was present in 32% of 47 Aboriginal children and 7% of 120 non-Aboriginal children aged 12 months or more.TEOAE responses were present in 90% (46/51) of Aboriginal children and 99% (120/121) of non-Aboriginal children aged <1 month and in 62% (21/34) and 93% (108/116), respectively, inAboriginal and non-Aboriginal children at age 1–2 months. Aboriginal children who failed TEOAEat age 1–2 months were 2.6 times more likely to develop OM subsequently than those who passed.Overall prevalence of type B tympanograms at field follow-up was 50% (n = 78) in Aboriginalchildren and 20% (n = 95) in non-Aboriginal children.